Pemanfaatan Microsoft Office 2016 Dalam Mengolah Data - Rivalri Kristanto Hondro; Nelly Astuty Hasibuan; Alwin Fau (Forum Kerjasama Pendidikan Tinggi, 2022)
SMA NEGERI 1 STM Hilir is one of the public schools that is domiciled on Jln Pendidikan Dusun 1, Talun Kenas Village, STM Hilir District, Deli Serdang Regency. Data processing at this school already uses the Microsoft Excel application but can only be operated by the school admin. Some of the teachers at SMA Negeri 1 STM Hilir still depend on admin staff to process their student grade data, thus making admin staff sometimes experience difficulties. The cause of this is due to the lack of teacher knowledge in utilizing/using the Microsoft Excel application in processing data. So through this community service activity the Team hopes to be able to provide knowledge related to the use of Microsoft Excel to teachers of SMA Negeri 1 STM Hilir so that these teachers are no longer dependent on the admin at school.